Caucasian and African American racial disparity in neonatal hospital mortality - Burdjalov, Maria; Qattea, Ibrahim; Nandakumar, Vanishree; Mohamed, Mohamed A.; Aly, Hany (Frontiers in Pediatrics, 2024)
Objective To examine disparity in hospital mortality among Caucasian (C) and African American (AA) neonates born at different gestational ages (GA). Methods De-identified national inpatient data were obtained from the Healthcare Cost and Utilization Project (HCUP) from the Agency for Healthcare Research and Quality (AHRQ) for the years 2011–2018. We compared the odds ratio for mortality among C and AA infants by sex and GA category. Analyses were repeated after controlling for multiple maternal and neonatal confounding variables in a logistic regression model. Results The study included 18,758,233 infants; 78.3% of them were C and 21.7% were AA. Compared to C population, AA population has a significantly higher mortality in term infants born at GA ≥ 36 weeks. The racial/ethnic disparity in preterm infants was inconsistent without any difference at 35–36 weeks in male and female infants. The overall aOR for mortality in AA in all male preterm infants ≤36 weeks was 1.44 (1.39–1.49), <0.01; and the overall aOR for mortality in AA in all preterm female infants ≤36 weeks was 1.38 (1.33–1.44). Conclusion Racial/Ethnic disparity in hospital mortality exists with higher AA mortality in infants born with GA > 36 weeks and less AA mortality in infants born with GA 24–26 weeks.